Nano-chitosan Spray as a Preservative and Food Security of Fishery Products in The Middle of the Covid-19 Pandemic - Dion Saputra; Ferra Robiatul Ula; Ajeng Budiarahma Nur Fadhila; Yosi Yananda Sijabat; Abista Ahmad Romadoni; Seto Windarto (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchThe author mentioned 2 highlights from their results research Nano-chitosan has the best susceptibility to bacterial strains of E. coli, S. enteritidis, L. monocytogenes, B. cereus and S. aureus.Nano-chitosan showed higher degree of inhibition than that done by chitosan. AbstractThe COVID-19 pandemic has impacted the fisheries sector, a decline in exports and fishermen's income caused by the disconnection of the marketing chain due to lockdown implementation in several export destination countries. Fish is a source of protein and as perishable goods, it experiences quality damage due to spoilage, commonly caused by hampered distribution of catches. Natural preservatives are needed to preserve catch so it won't get spoiled and can be accepted by consumers in suitable conditions for consumption. This study aims to evaluate the particle size of nano-chitosan and determine the effectiveness of nano-chitosan spray with different concentrations as a natural preservative in caught fish. This research method begins with making chitosan through 3 stages: demineralization, deproteination, and deacetylation. Chitosan was made into nano-chitosan with various concentrations of 3:1, 4:1, and 5:1 using ionic gelation. Nano-chitosan underwent several tests, including PSA, antibacterial activity by disc diffusion, organoleptic, and the effectiveness of preservatives. Antibacterial activity of nano-chitosan was able to inhibit Bacillus subtilis at three different concentrations, the potential to inhibit Escherichia coli was optimal at 5:1 treatment. The effectiveness of nano-chitosan preservative bacteria inhibition at three different concentrations proved to be sufficient to be used to extend shelf life and ensure the safety and quality of fishery products. The best concentration of nano-chitosan was 3:1 treatment. Nano-chitosan spray from crab shell waste has good antibacterial activity and preservative effectiveness. It could serve as an antibacterial agent and natural preservative for fishery products during the COVID-19 pandemic.